Effect of glutamine, glucose unhidrate and Moringa oleifera on blood lymphocytes in white mice (Rattus Novergicus) Wistar strain, following induction of a protein energy-deficient diet - Septa Katmawanti; Moch Yunus; Ari Wibowo Kurniawan; Anita Sulistyorini; Rosuzeita Fauzi; Supriyadi Supriyadi; Dea Amanda Caressa; Dea Aflah Samah; Oktavia Sri Wahyuni; Aquila Ghafril Azizah (AOSIS, 2022)
The aim of this research was studied the influence of giving Glutamine, Glucose Unhydrate and Moringa oleifera the blood lymphocyte of white rat (Rattus novergicus) Strain Wistar that was induced with protein energy malnutrtion (PEM). This was an experimental study with Completely Random Design, sample was white rats in PEM induced with parched rice for 15 days and those with normal diet with total 30 sample. The concluded is that there was a significant difference in the blood lymphocytes of white rats (Rattus novergicus) Strain Wistar gived glumorry with sig. (0.000) and glutamin + glucose unhydrate with sig. (0.001), while in the group gived Moringa oleifera there was no significant difference with sig. (0.076). Glumorry intervention has the highest level of significance by 19,2382 × 103/mm3 compared to all treatment groups. This suggests that the glumorry (Glucose Unhydrate, Glutamine, and Moringa oleifera) intervention successfully increased the lymphocyte count higher in the study sample with PEM condition compared to the group that was only given Glucose Unhidrat + Glutamine and the group that was only given Moringa Oleifera.